Judicial form of the special examination of air ships of civil aviation of Ukraine - Радзівон, С. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article opens up to the feature of judicial form of the special examination of air ships of civil aviation of Ukraine, rules of his leadthrough, rules of leadthrough of pre-flight and after-flight examinations of air ship, methods of leadthrough of the special examination of air ship on wing, control and safety of handluggage, luggage, load, mail and side припаса of air ship on internal and international lines, personal control of passengers and members of crew, maintenance of act discovered and withdrawn for the passenger (member of crew) of civil air ship of objects and things, forbidden for transporting.